Aplicação de processo assistido por simulação para a purificação de proteína recombinante obtida em plataforma de expressão detoxificada - Paiva, Thiago David de (2024)
The production of biopharmaceuticals, including vaccine components, involves the cultivation of cells in which the product is synthesized, followed by a sequence of recovery and purification steps which purpose is to eliminate impurities and obtain the product with the purity required for therapeutic use. The costs of purification operations vary from 20 to 80% of the overall cost of the process of obtaining biotechnological products, and are the determining factor in the price of the final product. In this study, a series of studies were carried out to develop a less complex and expensive purification process for Pneumococcal Surface Protein A (PspA4Pro), a promising component for the formulation of anti-pneumococcal vaccines, produced by ClearColi® cells. This Escherichia coli strain is genetically modified, free of endotoxic activity, offering less risk of adverse reactions caused by the endotoxins present in conventional E. coli strains. The development of purification processes for the protein of interest, without the addition of a tag, present in real cell clarification, allowing it to be scaled up and applied in industrial processes, was the main objective of the work. All the biomass used in the studies were obtained from previous ClearColi® cultivations and were available on site. An approach based on modeling and simulation of the main purification step, anion exchange chromatography, was used to select the optimum operating conditions, an innovative, economical and faster strategy compared to the trial and error method used in previous works to improve process efficiency. Initially, simulations of the mathematical model developed previously to describe the purification of PspA4Pro obtained in conventional E. coli culture by anion exchange chromatography were carried out, which adequately described the fractions eluted during the purification of the same protein obtained in ClearColi® cultures. New model simulations were then carried out to define promising purification strategies, which were conducted at the Vaccine Development Laboratory of Butantan Institute in São Paulo. Six purification processes were carried out, with the main stages being: cell disruption using a high-pressure homogenizer, with the operating pressure varying between 500 and 1200 bar; precipitation with cetyltrimethylammonium bromide (CTAB) at 1 mg.mL-1 ; clarification by centrifugation at 10000 rpm for 1 hour at 10°C; anion exchange chromatography of the cell clarified on Q-Sepharose resin coupled to an Äkta Avant 150 chromatograph and cryoprecipitation at pH 4.0 for a minimum of 24 hours at -20°C. The bicinchoninic acid (BCA) method was used to quantify total soluble proteins and SDS-PAGE was used to obtain the purity of the protein of interest using band densitometry. It was used the elution protocol with concentrations of 100, 250 and 1000 mmol.L-1 of NaCl, which proved to be the most efficient according to the results of the anion exchange chromatography simulation. By adopting this operating strategy for the chromatographic stage, followed by fractionation of the elution in which the intermediate concentration of NaCl was used and cryoprecipitation of the initial subfractions of the elution mentioned, it was possible to achieve purities over 95% of PspA4Pro. The work also showed that obtaining higher purities of the desired protein can be accompanied by lower recovery values.